Komunikasi Pemberdayaan Masyarakat dalam Pendampingan Masyarakat Perhutanan Sosial pada SSF Project Indonesia - Putri Azka Fatihatunnizma; Dede Lilis Chaerowati (UNISBA Press, 2024)
Abstract. Strengthening of Social Forestry (SSF) Project Indonesia is one of the efforts to accelerate the Social Forestry Program through strengthening community capacity, institutions in managing forest resources sustainably, and strengthening Social Forestry regulations. In this case, SSF Project Indonesia involves Community Facilitators/Field Facilitators who are key in the mentoring process. However, there are certainly many obstacles faced by Field Facilitators in conducting communication approaches to convince local communities so that this research is interesting to study. This research aims to describe empowerment communication in community assistance in 5 SSF Project Indonesia work areas. The theory used is Community Empowerment Theory. This research uses qualitative research methods with a case study approach, as well as a constructivist paradigm. Data collection techniques were carried out by interview, non-participant observation, literature & documentation study. The research subjects were determined based on purposive sampling technique, namely the Directorate of PKPS, SSF Project Indonesia Team Leader, and Field Facilitators. Data analysis techniques used from Miles & Huberman are data reduction, data presentation, & conclusion drawing/verification. The data validity test in this research is source triangulation. Abstrak. Strengthening of Social Forestry (SSF) Project Indonesia merupakan salah satu upaya untuk mempercepat Program Perhutanan Sosial melalui penguatan kapasitas masyarakat, kelembagaan dalam mengelola sumberdaya hutan secara lestari, serta memperkuat regulasi Perhutanan Sosial. Dalam hal ini, SSF Project Indonesia melibatkan Pendamping Masyarakat/Field Facilitator yang menjadi kunci dalam proses pendampingan. Namun, tentunya banyak kendala yang dihadapi oleh para Pendamping Masyarakat dalam melakukan pendekatan komunikasi untuk meyakinkan masyarakat setempat sehingga penelitian ini menarik untuk diteliti. Penelitian ini bertujuan untuk mendeskripsikan komunikasi pemberdayaan dalam pendampingan masyarakat di 5 areal kerja SSF Project Indonesia. Teori yang digunakan Teori Pemberdayaan Masyarakat. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus, serta paradigma konstruktivis. Teknik pengumpulan data dilakukan dengan wawancara, studi pustaka & dokumentasi. Subjek penelitian ditentukan berdasarkan teknik purposive sampling, yakni pihak Direktorat PKPS, Team Leader SSF Project Indonesia, dan Pendamping Masyarakat. Teknik analisis data yang digunakan dari Miles & Huberman berupa reduksi data, sajian data, & penarikan kesimpulan/verifikasi. Uji keabsahan data pada penelitian ini adalah triangulasi sumber.